You can do! : [videorecording (DVD)] : abs, featuring the stability ball - Sansone, Leslie; Pozo, Cal (Good Times Entertainment, 2004)
Leslie shows you the most effective ways to use your stability ball, plus three different workouts that will add variety and results.